PERBEDAAN DAYA TAHAN JANTUNG PARU ANTARA SISWA ORANGTUANYA PEGAWAI NEGERI DENGAN PETANI/NELAYAN - Budiman Budiman (Jurnal Dedikasi Pendidikan, 2020)
Students who attend BIna Generasi Bangsa Junior High School come from different parental backgrounds, both from civil servants and farmers and even fishermen. The hypothesis is "there are differences in endurance of the pulmonary heart between students whose parents are civil servants and farmers / fishermen in Bina Generasi Bangsa Junior High School students. The research method is comparative research. The stratified random sampling sample consisted of 31 students whose parents were civil servants and 31 students whose parents were farmers / fishermen. The technique of collecting test data ran as far as 2.4 km. "T" test data processing technique. Based on the results of the study obtained the category of pulmonary endurance of students whose parents are employees with a percentage of 93.55% and the average is 11.04. Students whose parents are fishermen / farmers are in the medium category with a percentage of 100% with an average of 11.64. The results of data analysis of differences in endurance of the pulmonary heart obtained t-count of 0.55 while t-table at 95% confidence level of 1.70, it can be said t-count of 0.55 ≥ t-table 1.70 then the research hypothesis is rejected the truth. That there is no difference between heart endurance between students whose parents are civil servants and students whose parents are fishermen / farmers in SMP Bina Generasi Bangsa